Metodologia para calibração do modelo hidrológico DHSVM - Mendes, Helder de Amorim (2016)
In this work the Distributed Hydrology Soil Vegetation Model was studied in order to propose an automatic calibration tool for the same. The basic principle of the implemented calibrator is the use of Clustering Search meta-heuristic (CS) that has the feature to produce a set of sub-optimal solutions, resulting from the calibration process. This solutions are used for verification of the possibility to improve the calibration of a given sub-basin by applying the solutions obtained for a number of other sub-basins. The tool and methodology of the proposed combination were applied to the calibration of a basin in southeastern Brazil formed by a set of sub-basins whose drains are monitored. The results show that both the tool and the methodology of combination proposed are effective, leading to a considerable improvement in the modeling resutaldos for the basin.